Structural and functional characterization of retinal impairment in T1DM patients without diabetic retinopathy: a 3-year longitudinal study - Sacconi, Riccardo; Tombolini, Beatrice; Cartabellotta, Antonio; Zerbini, Gianpaolo; Bandello, Francesco; Querques, Giuseppe (Acta diabetologica, 2024)
Purpose To analyze the progression of structural and functional retinal impairment in type 1 diabetes mellitus (T1DM) patients with no clinical signs of diabetic retinopathy (DR) during a 3-year follow-up. Methods This was an observational longitudinal study. Post-pediatric T1DM patients without clinical signs of DR, and sex- and age-matched healthy subjects were recruited at San Raffaele Hospital (Milan, Italy). Each patient underwent a comprehensive ophthalmological evaluation, including optical coherence tomography (OCT), OCT-angiography (OCT-A), retinal static and dynamic vessel analysis (DVA), and microperimetry. Results 21 eyes of 21 T1DM patients (10 females; 24 ± 2 years old), and 21 age and sex-matched healthy subjects were enrolled. At baseline, T1DM eyes revealed a significantly decreased vessel length density using OCT-A (p < 0.001 and p = 0.046 in 3 × 3 and 6 × 6 mm images) and a significantly increased vessel density index (p = 0.013 and p = 0.087 in 3 × 3 and 6 × 6 mm images) of deep capillary plexus. DVA detected a significantly decreased vessel response to flicker light (p = 0.002). A significantly increased thickness of ganglion cellular layer 6-mm-diameter subfields in inferior and superior quadrants was found in diabetic patients (p < 0.001 in both subfields). At 3-years-follow-up no significant longitudinal changes were disclosed in all analyses. Conclusions Concomitant subclinical microvascular and neurodegenerative damages could be early signs of DR onset that precede functional alterations and clinical signs of DR development. These alterations demonstrated a stable trend over time.